Theatricalising Democracy: The Language of Light in the Stage Production of Ben Binebaias If Nota A Play of the Gods (Global Journal of Human-Social Science, 2014)
This paper examines the appropriation of the aesthetics of stage lighting as an agency of narratology and communication in theatre. As a communicative art, theatre thrives fundamentally on verbal and none verbal communication. It speaks in many possible ways. But most people hold the wrong notion that the centre of communication in drama and theatre is the written word. Technical inputs such as scenographic art, costume and make up, stage lighting and sound are theatrical elements seen by most people within and outside the school of theatre as decorative arts that only assist to dramatise a play without significance given to them as forms of expression. This paper argues that all other departments and compartments of the theatre are directly involved in the language system of the theatre; the written and spoken words do not stand apart. This implies strongly that theatrical communication is a collective communication of words and para-verbal and non word communication arts. It is against this setting that the paper attempts to explore the aesthetics of light as a language of communication in the stage realisation of democracy in Ben Binebai's Drama, If Not... A Play of the Gods by the final year students of the Department of Theatre Arts, Niger Delta University. The paper concludes that stage lighting is an effective aesthetic power that clearly unfolds the deeper, meanings, intention, mood and temperament of an organized spectacle on the legitimate space.
Keywords: theatricalism; technical theatre; theatre; democracy; language; light; stage production